Evaluating and extending user-level fault tolerance in MPI applications. (August 2016) - Laguna, Ignacio; Richards, David F; Gamblin, Todd; Schulz, Martin; de Supinski, Bronis R; Mohror, Kathryn; Pritchard, Howard
The user-level failure mitigation (ULFM) interface has been proposed to provide fault-tolerant semantics in the Message Passing Interface (MPI). Previous work presented performance evaluations of ULFM; yet questions related to its programability and applicability, especially to non-trivial, bulk synchronous applications, remain unanswered. In this article, we present our experiences on using ULFM in a case study with a large, highly scalable, bulk synchronous molecular dynamics application to shed light on the advantages and difficulties of this interface to program fault-tolerant MPI applications. We found that, although ULFM is suitable for master–worker applications, it provides few benefits for more common bulk synchronous MPI applications. To address these limitations, we introduce a new, simpler fault-tolerant interface for complex, bulk synchronous MPI programs with better applicability and support than ULFM for application-level recovery mechanisms, such as global rollback.